(untitled) (Revista Iberoamericana de Bioética, 2020)
The reasons why the WHO European Office’s Health 2020 programme included strengthening resilience among its top four priorities in 2012 have become dramatically evident, as we make daily efforts to tackle the COVID-19 pandemic. Resilience is also established as a fundamental prerequisite not only to boost health but also to fulfil the 2030 Agenda and the SDGs as a whole. Resilience provides us with opportunities for positive, environmentally sustainable, and lasting change in the face of the changing reality that surrounds us.